Evaluation of Antibacterial and Antifungal Properties of Alchornea laxiflora (Benth.) Pax. & Hoffman - Akinpelu, David A; Abioye, Emmanuel O; Aiyegoro, Olayinka A.; Akinpelu, Oluseun F.; Okoh, Anthony I (Evidence-Based Complementary and Alternative Medicine, 2023)
International Journal of Evidence-based Complementary and Alternative Medicine,Page 7